PENINGKATAN KAPASITAS PRODUKSI MELALUI PENERAPAN TEKNOLOGI TEPAT GUNA DAN PENILAIAN KANDUNGAN GIZI MIE KELOMPOK SEJALAN - Harly, Resolinda; Febrianti, Firshty; Dwijatmoko, Muhammad Isa; Asnadeli, Asnadeli; Susantia, Elvi (Universitas Mataram, 2025)
The Sejalan Group is a bundo kanduang organization in Nagari Simalanggang, Lima Puluh Kota Regency, with 13 members. The Sejalan Group carries out business activities, one of which is processing noodles made from fruit, vegetables and other food ingredients. The problems faced by the Sejalan Group are low production capacity, relatively long production time, and the lack of nutritional information on the packaging. The solution to these problems is to provide a mixer and roll press machine with a capacity 10 kg of each, as well as conducting an analysis of the nutritional content of the noodles. The results of the activity show that production time efficiency is achieved because the mixing process is faster and more even than manually, consistency of noodle quality is obtained because the dough is more homogeneous so that the noodles have a uniform color, texture and thickness. The production scale increases because the Sejalan Group can start producing noodles in larger quantities in one process, so it is able to meet consumer demand and reach a wider market. Noodle quality analysis is carried out on samples of chicken variant noodles with added spinach as the Sejalan Group's flagship product. The analysis showed that the chicken noodle variant with added spinach contained an average protein content of 14.94%, fat content of 3.21%, water content of 8.81%, ash content of 2.34%, and crude fiber content of 0.69%. These results indicate that the Sejalan Group noodles meet the Indonesian National Standard (SNI 8217:2015) for dry noodles